Internal carotid artery aneurysm in skull base osteomyelitis: does the pattern of cranial nerve involvement matter?. Issue 10 (12th July 2018) - Hassannia, F; Carr, S D; Yu, E; Rutka, J A
Abstract: Objective: Carotid artery aneurysm is a potentially fatal complication of skull base osteomyelitis. It is important to know the warning signs for this complication, as early diagnosis is of great importance. This report aimed to determine whether the pattern of cranial nerve involvement may predict the occurrence of aneurysm involving the internal carotid artery in skull base osteomyelitis. Methods: Two diabetic patients with skull base osteomyelitis were incidentally diagnosed with pseudo-aneurysm of the petrous internal carotid artery on follow-up magnetic resonance imaging. They presented with lower cranial nerve palsy; however, facial nerve function was almost preserved in both cases. Computed tomography angiography confirmed aneurysms at the junction of the horizontal and vertical segments of the petrous carotid artery. Results: Internal carotid artery trapping was conducted using coil embolisation. Post-coiling magnetic resonance imaging demonstrated no procedure-related complications. Regular follow up has demonstrated that patients' symptoms are improving. Conclusion: One should be mindful of this potentially fatal complication in skull base osteomyelitis patients with lower cranial nerve palsies, with or without facial nerve involvement, especially in the presence of intracranial thromboembolic events or Horner's syndrome.